The tadpole of the Brazilian torrent frog Hylodes heyeri (Anura; Hylodidae) - Costa, T. R. N.; Lingnau, R.; Toledo, L. F. (Zootaxa, 2009)
Hylodes heyeri Haddad, Pombal & Bastos is allocated in the H. lateristrigatus group (Heyer, 1982), together with other 17 species. The tadpole of H. heyeri is still unknown and our aim here is to describe the tadpole and compare it with other Hylodes species for which tadpole descriptions are available.